Kahan Peningkatan Struktur Jalan Rel Dalam Rangka Menambah Frekuensi Pelayanan Angkutan Kereta Api Lintas Jember-Banyuwangi - Rahayu, Siti; Sianipar, Arbi (Warta Penelitian Perhubungan, 2010)
In order railway revitalization in Java Island and increasing of regional autonormJ are requiredresearches which could raises potential area supported by mode transport reliability.]ember is a producing regions of tobacro, coffee, resin, plate stone which located in DAOP 9 /emberand not supported road transport yet, operational performance is decreasing caused btj field constraints,"both infrastructure and supporting infrastructure nor its means.This research use field observation method, grmvth-demand analysis and doing calculation based onJormu.las railwmj technique which the result described as description.The result of this research shmvs if R.33 and R.42 wood/iron sleeper replaced with R.54 concretesleeper that securihj, safehJ and comfortable im.11 be better, Jember-Kalisat passed with maximumspeed 41,5 kmjhour could be 120 km;haur, Kalisat-Kalibaru passed with maximum speed 38,2 km/hour could be 80 kmjhour, Kalibaru-Temuguruh passed with maximum speed 48 km;haur could be110 kmjhour, Temuguruh-Banyuwangi Baru passed with maximum speed 64,7 km;haur could be120 kmjhour. Average of frequencij is nmv just 16 train set/datj will be 100 train set/datj, it meansjournei; from /ember to Banyuwangi will be passed in an hour and half hourKey Word: Increasing rail structure